2013 Low-Income Countries Global Risks and Vulnerabilities Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
An assessment of vulnerabilities and risks in LICs remains important both for LICs themselves and for the international community. There are currently 74 LICs, eligible for concessional financing from the Fund. This group of countries has a total population of about 1.3 billion, with an average per capita income of around USD 850. They typically face the steepest challenges in meeting the Millennium Development Goals (MDGs) and are increasingly the focus of global development assistance to assist them in this endeavor. This report serves several purposes. It provides a cross-cutting analysis of the economic vulnerabilities of LICs, yielding some general policy conclusions and messages aimed at strengthening their resilience to external shocks. It delivers a richer coverage of developments in LICs than is typically contained in the major IMF multilateral surveillance reports, where analysis is focused primarily on developments in the advanced and emerging market economies. The report serves as an effective outreach tool to country authorities and the wider public. Finally, it provides useful information to other international financial institutions (IFIs) and donors that provide financial resources to LICs on the potential financing needs of these countries under varying global scenarios.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet